Biological Procedures Online - Li, Shulin
Biological Procedures Online publishes articles that improve access to techniques and methods in the medical and biological sciences. We are also interested in short but important research discoveries, such as new animal disease models. Topics of interest include, but are not limited to: Reports of new research techniques and applications of existing techniques Technical analyses of research techniques and published reports Validity analyses of research methods and approaches to judging the validity of research reports Application of common research methods Reviews of existing techniques Novel/important product information Biological Procedures Online places emphasis on multidisciplinary approaches that integrate methodologies from medicine, biology, chemistry, imaging, engineering, bioinformatics, computer science, and systems analysis. The journal welcomes manuscripts from innovators who have overcome technical challenges or developed new methods.